ANALYSIS OF NaOCl CONTENT OF HAND & BODY LOTION AND FACE WASH CREAM BY IODOMETRIC TITRATION METHOD - Jeli Marlita; Yuyun Febriani; Risma Hayatun Nufus; Muhlisun Azim; Baiq Maylinda Gemantari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Cosmetics are needed by the public, such as hand and body lotions and face brightening creams, and there are many misuses of hazardous chemicals in cosmetics, including lotions and face brightening creams. Sodium hypochlorite, a  hazardous chemical, can cause skin damage, such as irritation, rash, hypersensitivity, and burns. The purpose of this study was to determine the presence of sodium hypochlorite compounds and sodium hypochlorite in hand and body lotion cosmetics and face brightening cream. The method used in this research was qualitative analysis with color reaction and quantitative analysis with iodometric titration. The results qualitatively showed that color changes occurred in all samples. NaOCl concentration in hand and body lotion at 0.2% concentration showed an average NaOCl concentration of 3.263 % ± 0.25 and face brightening cream concentration at an average concentration of 10 mg showed NaOCl levels of 88.933 % ± 7.57. Based on this, it was concluded that in the samples of hand and body lotion and face brightening cream, sodium hypochlorite compounds with different levels. Therefore, these samples could have side effects and toxicity in their usefulness as cosmetics. Keywords: Hand & body lotion, face brightening cream, sodium hypochlorite (NaOCl), iodometric titration